CO2 adsorption–desorption performance of mesoporous zirconium hydroxide with robust water durability. Issue 4 (4th January 2016) - Kamimura, Y.; Endo, A.
Abstract : The present study demonstrates for the first time, the development of mesoporous zirconium hydroxide with high CO2 capacity and sustainable adsorption–desorption performance within a broad range of pressures (100–3000 kPa). Abstract : The present study demonstrates for the first time, the development of mesoporous zirconium hydroxide with high CO2 capacity and sustainable adsorption–desorption performance within a broad range of pressures (100–3000 kPa). Mesoporous zirconium hydroxide with a high surface area of ∼400 m 2 g −1 was prepared by a simple and easy-to-handle precipitation route. The prepared high surface area mesoporous zirconium hydroxide exhibited significantly higher CO2 adsorption uptake and working adsorption capacity on a volumetric basis within a wide range of operating pressures of 100–3000 kPa than commercially available zeolite 13X. Reversible CO2 desorption was easily achieved by a pressure swing at moderate temperatures (298.15 K). Additionally, the prepared mesoporous zirconium hydroxide was adequately stable and strong to effectuate CO2 capture over multiple adsorption–desorption cycles without major reductions in its CO2 adsorption capacity. Furthermore, the effect of co-adsorbed water on the CO2 adsorption properties of mesoporous zirconium hydroxide was investigated. In the presence of co-adsorbed water, mesoporous zirconium hydroxide displayed reversible CO2 adsorption–desorption behavior in contrast to zeolite 13X that exhibited negligible CO2 adsorption within the wide range of pressures examined. The present study demonstrates the potential of high surface area mesoporous zirconium hydroxide toward efficient CO2 capturing processes.